Younger Dryas ice margin retreat triggered by ocean surface warming in central-eastern Baffin Bay. Issue 1 (December 2017) - Oksman, Mimmi; Weckström, Kaarina; Miettinen, Arto; Juggins, Stephen; Divine, Dmitry; Jackson, Rebecca; Telford, Richard; Korsgaard, Niels; Kucera, Michal
Abstract The transition from the last ice age to the present-day interglacial was interrupted by the Younger Dryas (YD) cold period. While many studies exist on this climate event, only few include high-resolution marine records that span the YD. In order to better understand the interactions between ocean, atmosphere and ice sheet stability during the YD, more high-resolution proxy records from the Arctic, located proximal to ice sheet outlet glaciers, are required. Here we present the first diatom-based high-resolution quantitative reconstruction of sea surface conditions from central-eastern Baffin Bay, covering the period 14.0–10.2 kyr BP. Our record reveals warmer sea surface conditions and strong interactions between the ocean and the West Greenland ice margin during the YD. These warmer conditions were caused by increased Atlantic-sourced water inflow combined with amplified seasonality. Our results emphasize the importance of the ocean for ice sheet stability under the current changing climate. High-resolution proxy records are essential for understanding the interactions between ocean, ice sheet and atmosphere. Here the authors present a high-resolution record of Younger Dryas sea surface conditions in Baffin Bay and show that ocean surface warming triggered the retreat of Jakobshavn Isbræ ice stream.